Plausible Functional Diagnostics by Rational Echocardiography in the Assessment of Valvular Heart Disease - Role of Quantitative Echocardiography in the Assessment of Mitral Regurgitation - Hagendorff, Andreas; Stöbe, Stephan (Frontiers in Cardiovascular Medicine, 2022)
The echocardiographic assessment of valvular heart diseases is the basic analysis of valvular defects next to clinical investigation and stethoscopy. Severity of mitral regurgitation (MR) is usually estimated by an integrated approach using semiquantitative parameters and is still one of the biggest challenges of echocardiography. Quantitative echocardiographic analysis of MR severity often fails to describe comprehensible hemodynamic conditions. However, comprehensive echocardiography based on standardized image acquisition and proper image quality is per se able to properly assess hemodynamic parameter comparable to cardiac magnetic resonance tomography. This viewpoint focusses on the uncertainty of MR severity assessed by echocardiography in recent trials of interventional MR treatment. In addition, the necessity to provide plausible echocardiographic data for individual decision making is highlighted. Thus, plausible functional diagnostics by rational echocardiography is a prerequisite in patients with valvular heart diseases.